2018
DOI: 10.7759/cureus.2507
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Survival of Esophageal Cancer Patients in an American Cohort

Abstract: ObjectivesThis study seeks to delineate trends in esophageal cancer patients in an American cohort and, in particular, examine the impact of race and histology on survival.MethodsThe association between over 50 variables between histology and race subgroups was evaluated. Survival was calculated using Kaplan-Meier curves and a multivariable Cox regression analysis (MVA) was performed.ResultsPoorer survival was noted in black vs. white (193 ± 65 days vs. 254 ± 39, 95% CI 205-295, p=0.07) and squamous cell cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 29 publications
3
20
1
5
Order By: Relevance
“…O tipo histológico mais frequente é o carcinoma de células escamosas (CCE); porém, estudos internacionais mostram diminuição gradativa na incidência desse tipo de tumor, e elevação na frequência de adenocarcinoma [3][4][5][6][7] .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…O tipo histológico mais frequente é o carcinoma de células escamosas (CCE); porém, estudos internacionais mostram diminuição gradativa na incidência desse tipo de tumor, e elevação na frequência de adenocarcinoma [3][4][5][6][7] .…”
Section: Introductionunclassified
“…Com o intuito de aumentar a sobrevida e minimizar as complicações do tratamento, estratégias utilizando a radioterapia e a combinação de radioterapia à quimioterapia têm despertado o interesse da comunidade científica [10][11] . Entretanto, apesar do progresso nos últimos anos no tratamento do câncer de esôfago, a sobrevida dos pacientes, mesmo após ressecção completa, continua muito baixa, em razão do estádio avançado da doença ao diagnóstico [3][4][12][13][14] . Esse fato acontece, principalmente, por causa dos sinais do câncer só ocorrerem quando o tumor atingir volume suficiente para causar sintomas obstrutivos.…”
Section: Introductionunclassified
“…They concluded that adjuvant RT is associated with a significantly lower death risk hazard ratio (0.84 95%CI 0.73-97, p = 0.016) and disease-specific death risk hazard ratio (0.84 95%CI 0.72-0.97, p = .02). On multivariate analysis in an epidemiological study by Nassri et al [42], it was shown that the only significant factor which benefits survival is esophagectomy, i.e., the surgery itself. They reported that 16% of patients on neoadjuvant treatment had disease progression, and only 41% underwent definitive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal cancer (ECa) is an extremely aggressive malignancy, and more than 50% of patients present with a locally advanced or metastatic disease at diagnosis. 1,2 Currently, there is no clear standard of care for these patients. However, patients with locally advanced disease that is not suitable for surgery or chemoradiation, or those in poor clinical condition with multiple comorbidities, could still benefit from palliative treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Dysphagia, chest pain, gastrointestinal bleeding, asthenia, weight loss, fever, nausea, and vomiting are the most frequent symptoms, which worsen quality of life. 2,[7][8][9] Moreover, dysphagia can also dramatically reduce nutritional support and lead to malnutrition, anorexia, and dehydration. 10 Several effective options, such as intraluminal stents, brachytherapy, and endoscopic treatment of obstruction or stenosis with laser or cryotherapy, are available for symptom palliation.…”
Section: Introductionmentioning
confidence: 99%